Optimal dose of ramosetron in female patients with irritable bowel syndrome with diarrhea: A randomized, placebo‐controlled phase II study. Issue 6 (16th February 2017) - Fukudo, S.; Matsueda, K.; Haruma, K.; Ida, M.; Hayase, H.; Akiho, H.; Nakashima, Y.; Hongo, M.
Abstract: Background: Previous studies showed that 5 μg of ramosetron, a serotonin (5‐hydroxytryptamine: 5‐HT)‐3 receptor antagonist, is only effective in male patients with irritable bowel syndrome (IBS) with diarrhea (IBS‐D). We hypothesized that either dose 1.25, 2.5, or 5 μg of ramosetron would be effective in female patients with IBS‐D. Methods: This randomized, double‐blind, placebo‐controlled, phase II dose‐finding exploratory trial included 409 female outpatients with IBS‐D treated in Japan. They were administered oral placebo ( n =102), or 1.25 μg ( n =104), 2.5 μg ( n =104), or 5 μg ( n =99) of ramosetron once daily for 12 weeks after a 1‐week baseline period. The primary endpoint was monthly responder rates of global improvement of IBS symptoms in the first month. Secondary endpoints included global improvement in the other months, abdominal pain/discomfort, weekly mean changes in the Bristol Stool Form Scale (BSFS), and IBS‐QOL. Key Results: Middle dose (2.5 μg) of ramosetron significantly improved abdominal pain/discomfort at second month (62.5%, P =.002), third month (60.6%, P =.005), and the last evaluation point (63.5%, P =.002) and weekly BSFS ( P <.05) except at Week 8, 11, and 12 than placebo. IBS‐QOL did not change. Ramosetron induced more constipation than placebo. Conclusions & Inferences: The trial suggested that 2.5 μg of ramosetron is the most effective and least harmful option for treating female patients with IBS‐D (Clinicaltrials.gov ID: NCT01274000). Abstract : Effect of 5‐HT3 antagonist on irritable bowel syndrome with diarrhea (IBS‐D) was believed to be gender‐specific. However, is it due to the failure of finding optimal dose which is different between men and women? This randomized, placebo‐controlled dose‐finding study clearly showed that 2.5 μg of ramosetron which is a half dose for men is the most effective on several key outcomes in women with IBS‐D. Difference in optimal dose of 5‐HT3 antagonist on IBS‐D patients between men and women provides further research concept on the serotonergic regulation of brain‐gut interactions in humans.